The characteristics of hepatitis B surface antigen (HBsAg)‐negative hepatitis B virus (HBV) infection in Chinese blood donors: a follow‐up study of donors tested negative for HBsAg and reactive for simultaneous nucleic acid testing of HBV, hepatitis C virus, and human immunodeficiency virus. Issue 3 (5th February 2017) - Guo, Zhaofu; Fu, Ping; Yin, Yijin; Wang, Funeng; Yin, Yiqing; Wang, Jingxing; Liu, Yu
Abstract : BACKGROUND: The real infection status of hepatitis B virus (HBV) of hepatitis B surface antigen (HBsAg)‐negative yet nucleic acid test (NAT)‐positive blood donors is difficult to clarify. Detailed follow‐up study is needed for analyzing the infectivity of these blood donors. STUDY DESIGN AND METHODS: Blood donors who screened negative for HBsAg and reactive for simultaneous NAT of HBV, hepatitis C virus (HCV), and human immunodeficiency virus (HIV) were included in a follow‐up epidemiologic questionnaire survey and contributed follow‐up samples for further testing. The follow‐up samples were tested repeatedly for the serologic markers and HBV DNA. The genotypes and sequence mutations of HBV infected by 11 HBV DNA–positive donors were analyzed through the amplification and sequencing of HBV S region. RESULTS: Of the 46 donors included in this study, 89.1% were infected with HBV (41/46), including one (2.2%) window period infection, three (6.5%) recovered infections, and 37 (80.4%) occult HBV infections (OBIs). The S region of HBV was successfully amplified and sequenced for seven donors, five infected with Genotype B (71.4%), one with Genotype C (14.3%), and one with Genotype D (14.3%). Mutations in the S region were detected in four donors (57.1%) CONCLUSIONS: This is the first detailed study with multiple follow‐up testing of the HBV infection status among blood donors who were tested negative for HBsAg and reactive for simultaneous NAT of HBV, HCV, and HIV. Most of these donors were infected with HBV with very low viral load. Our findings indicate that it is important to improve the sensitivity of NAT so as to decrease the residual risk of transfusion‐transmitted HBV infection.